What actually is social accountability? - Aston, Thomas (Medium, 2021)
Figuring out “what is the work?” we actually do sounds like a simple task, but in fact, it’s surprisingly difficult.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização

Of zinc roofs and mango trees: tractors, the state and agrarian dualism in Mozambique - Cabral, Lídia (The Journal of Peasant Studies, 2021)
This paper reviews the latest mechanisation programme by the Mozambican government, asking how it is politically driven and how it shapes and is shaped by agrarian structures. Old ideas about agrarian dualism are reproduced today, albeit with a new language of public-private partnerships that are seen as potentially driving the modernisation of the peasantry. State-sponsored and privately-run service centres, featuring zinc roofed warehouses, are the government’s preferred route to modernisation, yet failing to reach the average farmer and understanding the motives and predicaments of private managers. Emerging small to medium farmers, who keep tractors under shady mango trees in their backyards, are also offering mechanisation services to their peers, which are instrumental to stepping up their production and commercial activities. The state’s push for mechanisation feeds uneven patterns of accumulation and social differentiation.
Publisher: Routledge _eprint: https://doi.org/10.1080/03066150.2020.1860026
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; agriculture / agricultura; government policy / politica governamental; private sector / setor privado

Signing of Grant Agreement with Mozambique: Contributing to the improvement of people’s living environment in Niassa Province through the construction of a rural water supply facility - JICA (2021)
On February 26, 2021, the Japan International Cooperation Agency (JICA) signed a grant agreement with the Government of the Republic of Mozambique in Maputo, to provide grant aid of up to 2.076billion yen for the Project for the Construction of a Rural Water Supply Facility in Niassa Province. Under this project, people’s living environment in Niassa Province will improve through installing a rural water supply facility, which will allow access to safe and clean water. It is expected that this project will lead to reduction of waterborne diseases and nutritional improvement. Measures to combat climate change will also be conducted, and this project will contribute to the achievement of SDGs Goals 3, 6, and 13.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; access to services / acesso a serviços; climate change / mudanças climáticas; infrastructure / infrastrutura

Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Accepted: 2021-02-02T10:30:54Z
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Ssebagereka, Anthony; Apolot, Rebecca Racheal; Nyachwo, Evelyne Baelvina; Ekirapa-Kiracho, Elizabeth (International Journal for Equity in Health, 2021)
This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; community scorecard (CSC) / cartão de pontuação comunitária (CPC); gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

Beyond state capacity: bureaucratic performance, policy implementation and reform - Williams, Martin J. (Journal of Institutional Economics, 2021)
There is a broad consensus that state capacity is central to economic and institutional development. But while the concept originated as a tool for macro-historical and comparative analysis, its success has led the term ‘capacity’ to become a default metaphor for discussing the quality of government bureaucracies. This paper discusses the limitations to conceiving of narrower questions of bureaucratic performance and policy implementation through the lens of the broad, aggregate concept of capacity. Whereas capacity refers to bureaucracies’ hypothetical potential, this usually differs from their actual actions due to internal information and incentive problems created by bureaucracies’ collective nature, and the constraints and uncertainty imposed by their multiple political principals. Capacity is a convenient shorthand term and is appropriate for some purposes, but it achieves this convenience by abstracting away from the mechanisms that determine bureaucratic performance and policy implementation. To advance the study of bureaucratic quality, researchers should seek to understand the implications of bureaucracies’ collective nature, engage with contextual specificity and contingency in policy implementation, and focus measurement and reform efforts more towards actual performance than hypothetical capacity.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; L - english / inglês; access to services / acesso a serviços

Health, development, and institutional factors: The Mozambique case - Garrido, Paulo Ivo (2020)
Abstract: The central aim of this text is to show the impact institutions have on the performance of the health sector in Mozambique. The text shows that of the social determinants of health, institutions play a central role in the performance of the Mozambican health sector—and, through it, economic and social development—particularly for the poorer and more vulnerable, such as children, women, the disabled, and the elderly. It is also argued that the deficiencies and inefficiencies of the operation of the health sector in Mozambique are largely the result of the fact that the institutions with influence on the health sector are controlled by a minority of privileged people who do not give the appropriate priority to the basic health needs of the majority of the population. Finally, it is argued that the most important institutional measures for improving the state of health of Mozambicans are the revision of the Constitution of the Republic, the strengthening of the National Health System (particularly the National Health Service), and the reduction of poverty and economic and social inequality.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Saúde, desenvolvimento e factores institucionais: o caso de Moçambique - Garrido, Paulo Ivo (2020)
Este texto tem por objectivo central mostrar o impacto que as instituições têm no desempenho do sector da Saúde em Moçambique. No texto demonstra-se que, de entre os Determinantes Sociais da Saúde, as instituições têm um papel central no desempenho do sector da Saúde — e, por seu intermédio, no desenvolvimento económico e social — dos moçambicanos, em especial dos mais pobres e mais vulneráveis, como as crianças, as mulheres, as pessoas com deficiência e os idosos. Argumenta-se também que as deficiências e ineficiências do funcionamento do sector da Saúde em Moçambique resultam em larga medida do facto de as instituições com influência no sector da Saúde serem controladas por uma minoria de privilegiados que não dá a prioridade devida às necessidades básicas em saúde da maioria da população. Finalmente, argumenta-se que as medidas de carácter institucional mais importantes para a melhoria do estado de saúde dos moçambicanos são a revisão da Constituição da República, o reforço do Sistema Nacional de Saúde (em particular do Serviço Nacional de Saúde) e a redução da pobreza e das iniquidades económica e social.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Baseline Assessment of Facility and District Capacity: Alcançar Qualidade de Serviços de Saúde para Mulheres e Crianças - USAID; fhi360; Alcançar (FHI 360, 2020)
The Alcançar Baseline Assessment of Facility and District Capacity was conducted to establish an evidence base against which to measure project performance and impact over the life of the project and to inform project priorities and planning. The assessment includes a census of health centers and hospitals in Nampula province - the population of facilities that the project is expected to influence. Trained data collection teams interviewed facility and district staff to collect current information on (1) facility infrastructure and policies, (2) human resources, (3) ordering and management of maternal and child health (MCH) commodities, (4) provision of MCH services (5) knowledge of MCH care components, and (6) emergency referral capacity. Additionally, they reviewed and extracted data from facility registers over a 6-month period and observed antenatal care (ANC) consultations. Data collectors visited each of the district health offices (Serviço Distrital de Saúde, Género, Criança e Acção Social, SDSMAS) to gather information on district health capacity to provide clinical mentoring, implement quality improvement and death audits, and manage commodities. This assessment report presents selected results.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; health - maternal and child / saúde - materno-infantil; health / saúde

Os Desafios da Expansão do Ensino Superior e a Formação do Capital Humano em Moçambique - Batone, Domingos Carlos (2020)
This research entitled “The Challenges of Expanding Higher Education and the Formation of Human Capital in Mozambique”, analyzes the quality, sustainability and democratization of Higher Education and its influence on the development of human capital. However, the results of this study show that despite the increase in the number of Universities, in several developing countries, such as Mozambique, many of the poorest people remain in the rural sector and tend to continue there for several decades, with the need to bring establishments closer together teaching communities. To reduce poverty, it is necessary to do something for this sector, the right thing to do is to educate the population until reaching a higher level and generate human capital. Based on the consulted literature, using bibliographic research, documentary research and relying on the Human Capital Theory, it was found that the experiences of successful countries depended on social stability, and this cannot be maintained when large portions of the population fall behind in education. Therefore, higher education in these areas cannot be just a way out, it must also be a way of ascending life to obtain more income and consequently foster development. In this sense, the conclusion was reached that higher education is the best way to reduce social inequalities and poverty in Mozambique, however, the sustainability, quality and democracy of higher education must be preserved.
Publisher: Unpublished
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; education / educação; poverty / pobreza; youth / juventude

‘We all have the same right to have health services’: a case study of Namati’s legal empowerment program in Mozambique - Schaaf, Marta; Falcao, Joana; Feinglass, Ellie; Kitchell, Erin; Gomes, Nadja; Freedman, Lynn (BMC Public Health, 2020)
Background: Legal empowerment and social accountability are two strategies that are increasingly used to address gaps in healthcare in low- and middle-income countries, including failure to provide services that should be available and poor clinical and interpersonal quality of care. This paper is an explanatory case study of a legal empowerment effort that employs community paralegals and trains Village Health Committees (VHCs) in Mozambique. The research objective was to explore how community paralegals solved cases, the impact paralegals had on health services, and how their work affected the relationship between the community and the health sector at the local level. Methods: The case study had two components: (1) a retrospective review of 24 cases of patient/community grievances about the health system, and (2) qualitative investigation of the program and program context. The case reviews were accomplished by conducting structured in-depth interviews (IDIs) with those directly involved in the case. The qualitative investigation entailed semi-structured Key Informant Interviews (KIIs) with district, provincial, and national health managers and Namati staff. In addition, focus group discussions (FGDs) were held with Health Advocates and VHC members. Results: Case resolution conferred a sense of empowerment to clients, brought immediate, concrete improvements in health service quality at the health facilities concerned, and seemingly instigated a virtuous circle of rightsclaiming. The program also engendered incipient improvements in relations between clients and the health system. We identified three key mechanisms underlying case resolution, including: bolstered administrative capacity within the health sector, reduced transaction and political costs for health providers, and provider fear of administrative sanction. Conclusions: This study contributes to the limited literature regarding the mechanisms of legal empowerment case resolution in health systems and the impact of hybrid legal empowerment and social accountability approaches. Future research might assess the sustainability of case resolution; how governance at central, provincial, and district level is affected by similar programs; and to what extent the mix of different cases addressed by legal empowerment influences the success of the program.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; empowerment / empoderamento; health / saúde

Social and Behaviour Change Communication Interventions in Mozambique - Cooper, Rachel (2019)
Social and behaviour change communication (SBCC) is the use of communication to change behaviours by positively influencing knowledge, attitudes and social norms at the individual and community level. Approaches to SBCC include, but are not limited to: media campaigns, peer educators and mentors, small group sessions, community dialogues and events, and digital tools. This rapid literature review focuses on SBCC interventions in Mozambique across four sectors: family planning (FP); girls’ empowerment; water, sanitation and hygiene (WASH), and nutrition. The most common SBCC approaches across the four sectors include: Inter-personal communication, Community participatory approaches, SMS based platforms, and Media channels. This review draws on evaluations of SBCC intervention, donor reports, and qualitative evidence collected by implementers and funders. There is a relatively large evidence base for FP and nutrition interventions, and a comparatively smaller one for WASH and girls’ empowerment. No lessons learned from integrating WASH and nutrition programming could be found during the course of this review. Although there are examples of nutrition programming including WASH in their counselling interventions, as well as calls for the development of multisectoral programmes. For example, in 2017, UNICEF signed a multi-sectoral proposal covering WASH, nutrition, and behaviour change funded by the EU. The programme will work in Nampula and Zambezia Provinces between 2017 and 2021.
Accepted: 2020-02-14T13:40:55Z Publisher: IDS
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; health / saúde; ⛔ No DOI found

Democratization of Health Services: Dynamics of Administrative Resistances (N'weti - comunicação para saúde, 2019)
This policy brief, apart from describing the dilemmas of the democratization process of health services it, aims to analyze its implications on the dynamics of social accountability in the health sector and, finally, to inform on possible ways for a more coherent democratization, considering the normative discourses
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; decentralization / descentralização; health / saúde

The State of ICT in Mozambique 2018 - Gillwald, Alison; Mothobi, Onkokame; Rademan, Broc (Research ICT Africa, 2019)
Mozambique has a challenging path ahead if it is to realise the full potential of the ICT sector in developing its economy and to make progress on the information communication technology targets that are intended as enabling the achievement of the United Nations’ Sustainable Development Goals. Mozambique’s successes include licensing and regulatory achievements in telecommunications, which have stimulated competition and contributed to meeting national policy objectives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; infrastructure - energy / infrastrutura - energia; infrastructure / infrastrutura

Religion and Use of Institutional Child Delivery Services: Individual and Contextual Pathways in Mozambique - Cau, Boaventura Manuel; Agadjanian, Victor (International perspectives on sexual and reproductive health, 2019)
CONTEXT: Research on institutional child delivery in Sub-Saharan Africa typically focuses on availability and accessibility of health facilities. Cultural factors, including religion, that may facilitate or hinder the use of such services have not been well examined and remain poorly understood. METHODS: The relationship between religious affiliation and delivery in a health facility was explored using data from a household survey of 1,297 women aged 18-50 and a census of 825 religious congregations, both conducted in a predominantly Christian district in Mozambique in 2008. Multilevel logistic regression analyses were conducted to predict the likelihood of recent institutional delivery according to both individual religious affiliation and the concentration of religious congregations of certain denominations in the community of residence. RESULTS: Approximately 63% of deliveries occurred in a health facility. The odds of such deliveries were lower among women who belonged to Apostolic churches or had no religious affiliation than among members of Catholic or mainline Protestant churches, net of other factors (odds ratios, 0.5 and 0.6, respectively). In addition, regardless of a woman's religion, the odds that she had an institutional delivery increased by 9% for each additional Catholic or mainline Protestant congregation in her community of residence (1.1). CONCLUSIONS: Organized religion is associated with critical health outcomes in Mozambique and, potentially, in other Sub-Saharan African contexts. Policymakers should consider designing programs and interventions that promote the use of institutional delivery services among members of religious groups characterized by low use of these services and in areas where such religious groups have a strong presence.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

The Health Budget: The Disparity Between Political Discourse and Practice - N'weti (N'weti, 2019)
Key Messages: - Health is a human right and is constitutionally protected in Mozambique; - The health sector is considered a priority sector by the Government of Mozambique; - The health sector is amongst the least funded by the State Budget in the past four years, (with less than 8% on average), against the 15% assumed in Abuja; - For the year 2014, of the 762.8 million USD allocated to the health sector, 44% came from external sources (REO MOH, 2014). The combined PROSAUDE resources, and the speci c "off-budget" projects’ funding demonstrates the enormous reliance on external partners to support the country’s health strategy; - There is an urgent need to increase internal State Budget funding for the health sector to ensure sustainability.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; budget / orçamento; health / saúde

Obstacles to advancing women’s health in Mozambique: a qualitative investigation into the perspectives of policy makers - Qiu, Mary; Sawadogo-Lewis, Talata; Ngale, Katia; Cane, Réka Maulide; Magaço, Amilcar; Roberton, Timothy (Global Health Research and Policy, 2019)
Background: Despite substantial investment in women’s health over the past two decades, and enthusiastic government support for MDG 5 and SDG 3, health indicators for women in Mozambique remain among the lowest in the world. Maternal mortality stayed constant from 2003 to 2011, with an MMR of 408; the estimated HIV prevalence for women of 15–24 years is over twice that for men; and only 12.1% of women are estimated to be using modern contraception. This study explores the perspectives of policy makers in the Mozambican health system and affiliates on the challenges that are preventing Mozambique from achieving greater gains in women’s health. Methods: We conducted in-depth interviews with 39 senior- and mid-level policy makers in the Ministry of Health and affiliated institutions (32 women, 7 men). Participants were sampled using a combination of systematic random sampling and snowball sampling. Participants were asked about their experiences formulating and implementing health policies and programs, what is needed to improve women’s health in Mozambique, and the barriers and opportunities to achieving such improvement. Results: Participants unanimously argued that women’s health is already sufficiently prioritized in national health policies and strategies in Mozambique; the problem, rather, is the implementation and execution of existing women’s health policies and programs. Participants raised challenges related to the policy making process itself, including an ever-changing, fragmented decision-making process, lack of long-term perspective, weak evaluation, and misalignment of programs across sectors. The disproportionate influence of donors was also mentioned, with lack of ownership, rapid transitions, and vertical programming limiting the scope for meaningful change. Finally, participants reported a disconnect between policy makers at the national level and realities on the ground, with poor dissemination of strategies, limited district resources, and poor consideration of local cultural contexts. Conclusions: To achieve meaningful gains in women’s health in Mozambique, more focus must be placed on resolving the bottleneck that is the implementation of existing policies. Barriers to implementation exist across multiple health systems components, therefore, solutions to address them must also reach across these multiple components. A holistic approach to strengthening the health system across multiple sectors and at multiple levels is needed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
978-1-78118-441-7
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Barómetro Municipal 2017. Relatório de dados quantitativos. - IESE (Instituto de Estudos Sociais e Económicos (IESE), 2018)
É o novo relatório de pesquisa produzido por uma equipa de investigadores do Instituto de Estudos Sociais e Económico (IESE), coordenada por Salvador Forquilha, no quadro de um projecto de investigação em curso sobre a avaliação dos munícipes em relação ao desempenho da governação municipal em Moçambique. Este primeiro “Barómetro da Governação Municipal 2017” (BGM) explora dados quantitativos relativos à percepção dos munícipes sobre as diferentes vertentes da actuação dos órgãos e serviços municipais e que podem permitir às autoridades municipais melhor conceberem os seus planos de governação e a responderem de maneira mais eficaz às expectativas dos munícipes. Refira-se que nesta primeira fase do projecto BGM foram abrangidos oito municípios, cobrindo diferentes regiões do país, nomeadamente Beira, Ilha de Moçambique, Lichinga, Manjacaze, Nampula, Pemba, Quelimane e Tete.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; governance / governação

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

An Exploratory Study of Four Urban Community Libraries in Nampula City, Mozambique: Do They Satisfy Community Informational Needs? - Szabo, Elizabeth Eva; Vieira, Ilidia (Libri, 2017)
This exploratory study describes the characteristics of four independent urban community libraries in Nampula city, located in northern Mozambique, East Africa. In a country where public library services are inadequately equipped to address the educational, informational and cultural needs of its citizens, the emergence of urban community libraries in the city indicates that the population is seeking better alternative sources of information. The study profiles four urban libraries to identify their role in the communities they serve and determine whether they conform to Mostert’s (1998) community library model. A case-study design was used with data collection techniques of structured interviews to collect qualitative data from library directors and librarians, a multiple choice questionnaire to obtain user responses, while further statistical data was obtained from collection, circulation and library user records. Findings indicate these four urban libraries only minimally adhere to Mostert’s model and are instead mimicking existing public and school libraries by catering to predominantly secondary and university level students. As a result, the educational, informational and cultural needs of other key groups in the community, such as the illiterate, neo-literate and disadvantaged, are ignored. This is due to a lack of trained library professionals and restrictive library policies.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; access to services / acesso a serviços; education / educação

Cidadania e Mudanças na Saúde e Educação em Moçambique: O Cartão de Pontuação Comunitária - Franco, Erika Lopez; Citizen Engagement Programme (CEP) (2017)
Este documento sumariza as aprendizagens feitas ao longo da implementação do Cartão de Pontuação Comunitária (CPC) no quadro do Programa Cidadania e Participação (CEP), o qual terminou em Dezembro de 2017. O CEP foi um programa de responsabilização social que tinha como objectivo final aumentar a influência dos cidadãos na melhoria da qualidade dos serviços de saúde e educação em Moçambique.
Accepted: 2018-04-13T12:59:17Z Publisher: (CEP) Citizen Engagement Programme / Cidadania e Participação
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; Northern PEA; access to services / acesso a serviços; citizenship & participation / cidadania e participação; community scorecard (CSC) / cartão de pontuação comunitária (CPC); education / educação; health / saúde

Maternal and Newborn Mortality: Community Opinions on Why Pregnant Women and Newborns Are Dying In Natikiri, Mozambique - Belo, C; Pires, P; Josaphat, J; Siemens, R; Rooke, E; Spence-Gress, C (International Journal of Research, 2017)
Background and objective: maternal and neonatal mortality rates in Mozambique are high, due to insufficient numbers of qualified health workers, lack of equipment and materials, referral system deficiency, difficulties to access health services and gender issues. This study assesses the barriers to health care access, regular attendance at ante natal consultations, institutional delivery and postnatal and neonatal follow-up. This is part of the baseline study for an implementation research project to reduce maternal and neonatal mortality in Natikiri, Nampula, Mozambique. Conclusion: local community members and health professionals were asked to state what they thought would be the best way to intervene. These ideas were then discussed further at a conference with health professionals and government representatives. Six intervention strategies to address identified problems were decided on and will be the basis for the ongoing implementation research project. They were: 1. Expanding family planning especially with adolescents. 2. Community based transport system for pregnant women. 3. Strengthening maternal and child health services by training maternity personnel in obstetrical emergency care and neonatal resuscitation. 4. Providing four quality prenatal visits. 5. Providing quality cesarean deliveries. 6. Supporting the Mozambican Government's campaign against bribery.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

Maternity care system in Maputo, Mozambique: Plans and practice? - Long, Qian; Madede, Tavares; Parkkali, Saara; Chavane, Leonardo; Sundby, Johanne; Hemminki, Elina (Cogent Medicine, 2017)
Mixed methods were used with various data sources to describe organisation and delivery of maternity care in Maputo city, Mozambique in early 2010s and to compare the plans with the service provision in practice. In the public health sector, maternity care was organised to be area based and hierarchical with a planned referral system. The provision of basic and emergency maternity care was publicly funded, largely dependent of donor funds, and free of charge for users. Even though Maputo City was better resourced than the rest of the country, there was a large lack of health professionals. Women’s choices and self-referrals, even to higher levels of care, were common, which broke the plans of areas responsibility, gate keeping and care by medical needs. Private services for maternity care had emerged for those who were able to pay, leading to dual practices of health professionals and shortage of care providers in the public system at odd hours. Information of maternity care was aggregate and poorly stored. The gap between “planned” services delivery and “practice” in a real-life requires overall health system strengthening to improve efficiency and effectiveness of health services delivery.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Desafio da articulação entre os cidadãos e os Comités de Qualidade e Humanização dos Cuidados de Saúde como órgãos de representação da comunidade - Dias, José (Centro de Aprendizagem e Capacitação da Sociedade Civil, 2017)
O Ministério da Saúde reconhece os Comités de Qualidade e Humanização dos Cuidados de Saúde nas Unidades Sanitárias como a principal forma de diálogo e ligação entre os serviços de saúde e as comunidades. Os Termos de Referência revistos, afirmam que o Comité de Qualidade e Humanização das Unidades Sanitárias constitui uma equipa de assessoria e coordenação ao processo de implementação da actividades de qualidade e humanização no âmbito da Unidade Sanitária. Destina-se a empreender uma política institucional de resgate de valores humanitários e de garantia de qualidade nos serviços de saúde, em benefício dos utentes e trabalhadores através da gestão participativa. Contudo, o sector de saúde dispõe também da Carta dos Direitos e Deveres do Doente, como instrumento que, no nosso entendimento, define o padrão da prestação de serviços, de comportamento, e concede espaço ao cidadão, individual ou colectivamente, para a exigência directa de serviços de saúde de qualidade. A este último propósito, por exemplo, cabe ressaltar que no quadro do Direito 16 (Direito a apresentar sugestões, queixas e reclamações) é estabelecido que através dos canais disponibilizados pelas Autoridades Sanitárias, os doentes têm direito a apresentar, individual ou colectivamente, petições, sugestões, reclamações ou queixas sobre a organização e o funcionamento dos serviços de saúde; e de ter as suas queixas atendidas prontamente e de maneira equitativa (MISAU, 2011). O que se apreende do exposto é que enquanto os Comités de Qualidade e Humanização funcionam numa lógica essencialmente de Democracia Representativa, a Carta dos Direitos e Deveres do Doente se insere numa abordagem de Democracia Participativa, buscando promover uma cidadania activa do doente/cidadão na sua interacção directa com as unidades sanitárias. O nosso artigo problematiza e discute as dinâmicas de representação e de participação activa do cidadão no processo da prestação de serviços de saúde. A nossa base de discussão é fundamentada em evidências de 15 distritos de actuação do Centro de Aprendizagem e Capacitação da Sociedade Civil (CESC), onde funcionam os Comités de Qualidade e Humanização, por um lado, e se implementa a abordagem de Responsabilização Social, usando ferramentas tais como Cartão de Pontuação Comunitária, por outro.
Keywords: G - Mozambique / Moçambique; Health PEA; L - portuguese / português; access to services / acesso a serviços; citizenship & participation / cidadania e participação; health / saúde

Barriers and facilitators to health care seeking behaviours in pregnancy in rural communities of southern Mozambique - Munguambe, Khátia; Boene, Helena; Vidler, Marianne; Bique, Cassimo; Sawchuck, Diane; Firoz, Tabassum; Makanga, Prestige Tatenda; Qureshi, Rahat; Macete, Eusébio; Menéndez, Clara; von Dadelszen, Peter; Sevene, Esperança (Reproductive Health, 2016)
Background: In countries, such as Mozambique, where maternal mortality remains high, the greatest contribution of mortality comes from the poor and vulnerable communities, who frequently reside in remote and rural areas with limited access to health care services. This study aimed to understand women’s health care seeking practices during pregnancy, taking into account the underlying social, cultural and structural barriers to accessing timely appropriate care in Maputo and Gaza Provinces, southern Mozambique. Methods: This ethnographic study collected data through in-depth interviews and focus group discussions with women of reproductive age, including pregnant women, as well as household-level decision makers (partners, mothers and mothers-in-law), traditional healers, matrons, and primary health care providers. Data was analysed thematically using NVivo 10. Results: Antenatal care was sought at the heath facility for the purpose of opening the antenatal record. Women without antenatal cards feared mistreatment during labour. Antenatal care was also sought to resolve discomforts, such as headaches, flu-like symptoms, body pain and backache. However, partners and husbands considered lower abdominal pain as the only symptom requiring care and discouraged women from revealing their pregnancy early in gestation. Health care providers for pregnant women often included those at the health facility, matrons, elders, traditional birth attendants, and community health workers. Although seeking care from traditional healers was discouraged during the antenatal period, they did provide services during pregnancy and after delivery. Besides household-level decision-makers, matrons, community health workers, and neighbours were key actors in the referral of pregnant women. The decision-making process may be delayed and particularly complex if an emergency occurs in their absence. Limited access to transport and money makes the decision-making process to seek care at the health facility even more complex.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Gaza; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

For an efficient, decentralised, transparent and inclusive health system - N'weti (N'weti, 2016)
Recommendations: 1. On planning and budgeting, greater coordination is recommended between planning (setting priorities) and budgeting (financial apportionment). Transformation of all District Health Services, Women and Social Action (SDSMAS) into Management Beneficiary Units (MBU) is necessary. 2. Stakeholders should bet more on application of national public financial management systems (PFM). The use of parallel financial systems instead of enabling the National Health System (NHS) to be more e cient hinders the enhancement of the sector’s PFM systems. 3. With regard to budgeting, zero-based budgeting implementation is recommended, replacing the incremental budgeting system. Zero-based budgeting is more realistic in so far as the health sector operation costs are concerned. 4. On the decentralisation and citizen participation component, the establishment of a national plan for decentralisation in the health sector is recommended. This plan would allow systematise local citizen participation mechanisms in the health system management and monitoring. 5. On revenue collection, the sector authorities need to explore areas of potential revenue already identified in Intellica’s 2013 research report, such as drug prescription, outpatient, medical certificate rates; and comply with the Decree 11/2007 of 30 May, which regulates tobacco consumption and sale, which has great potential to generate revenue for the health sector at the district level, by means of fines on the lawbreakers. 6. A Policy Brief drawn from the Public Expenditure Tracking Survey (PETS) in the Health Sector in Angoche, Bilene, Magude and Xai-Xai districts, and Chamanculo and José Macamo General Hospitals On expenditure performance, more and better coordination among stakeholders at district levels and Health Centres is recommended in order to avoid expenditure implementation costs in a fragmented and uncoordinated manner. 7. On procurement, accuracy improvement is recommended for the current legal framework implementation. This is to ensure that Procurement Management Units (PMUs) are practical; they can perform their tasks with independence, impartiality and professionalism. The direct award should always be treated as provided for in the law (an exception) and not deemed as the rule like what we have noticed occur in the researched cases. The document disorderliness of the Procurement Management Units portfolios can be solved with portfolio digitisation, ensuring more and better file and document handling, more control and additional transparency. 8. On transparency, recommendation to the Ministry of Health (MoH) is on the establishment of mechanisms which may ensure that sector o cials, who handle equal duties, should have the same understanding about procedures, not only in the health sector, but also in liaison with other sectors and society in general. When applying the Right to Information Act, Civil Society Organizations (CSOs) should now carry out awareness raising sessions and dialogue with sector o cials in order to reach mutual understanding on the added value that represents transparent public service management, with accountability and civil society influence, through monitoring and evaluation.
Keywords: *indexed; *non-public; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; GD - Bilene; GD - Magude; GD - Xai-Xai; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; budget / orçamento; decentralization / descentralização; health / saúde

Mapping the use of research to support strategies tackling maternal and child health inequities: evidence from six countries in Africa and Latin America - Vargas, Emily; Becerril-Montekio, Victor; Gonzalez-Block, Miguel Ángel; Akweongo, Patricia; Hazel, Cynthia N. A.; Cuembelo, Maria de Fatima; Limbani, Felix; Bernardo, Wanderley; Muñoz, Fernando (Health Research Policy and Systems, 2016)
Background: Striving to foster collaboration among countries suffering from maternal and child health (MCH) inequities, the MASCOT project mapped and analyzed the use of research in strategies tackling them in 11 low- and middle-income countries. This article aims to present the way in which research influenced MCH policies and programs in six of these countries – three in Africa and three in Latin America. Methods: Qualitative research using a thematic synthesis narrative process was used to identify and describe who is producing what kind of research, how research is funded, how inequities are approached by research and policies, the countries’ research capacities, and the type of evidence base that MCH policies and programs use. Four tools were designed for these purposes: an online survey for researchers, a semi-structured interview with decision makers, and two content analysis guides: one for policy and programs documents and one for scientific articles. Results: Three modalities of research utilization were observed in the strategies tackling MCH inequities in the six included countries – instrumental, conceptual and symbolic. Instrumental utilization directly relates the formulation and contents of the strategies with research results, and is the least used within the analyzed policies and programs. Even though research is considered as an important input to support decision making and most of the analyzed countries count five or six relevant MCH research initiatives, in most cases, the actual impact of research is not clearly identifiable. Conclusions: While MCH research is increasing in low- and middle-income countries, the impact of its outcomes on policy formulation is low. We did not identify a direct relationship between the nature of the financial support organizations and the kind of evidence utilization within the policy process. There is still a visible gap between researchers and policymakers regarding their different intentions to link evidence and decision making processes.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Challenges and opportunities for implementing evidence-based antenatal care in Mozambique: a qualitative study - Biza, Adriano; Jille-Traas, Ingeborg; Colomar, Mercedes; Belizan, Maria; Requejo Harris, Jennifer; Crahay, Beatrice; Merialdi, Mario; Nguyen, My Huong; Althabe, Fernando; Aleman, Alicia; Bergel, Eduardo; Carbonell, Alicia; et al. (BMC Pregnancy and Childbirth, 2015)
Background: Maternal mortality remains a daunting problem in Mozambique and many other low-resource countries. High quality antenatal care (ANC) services can improve maternal and newborn health outcomes and increase the likelihood that women will seek skilled delivery care. This study explores the factors influencing provider uptake of the recommended package of ANC interventions in Mozambique. Methods: This study used qualitative research methods including key informant interviews with stakeholders from the health sector and a total of five focus group discussions with women with experience with ANC or women from the community. Study participants were selected from three health centers located in Maputo city, Tete, and Cabo Delgado provinces in Mozambique. Staff responsible for the medicines/supply chain at national, provincial and district level were interviewed. A check list was implemented to confirm the availability of the supplies required for ANC. Deductive content analysis was conducted. Results: Three main groups of factors were identified that hinder the implementation of the ANC package in the study setting: a) system or organizational: include chronic supply chain deficiencies, failures in the continuing education system, lack of regular audits and supervision, absence of an efficient patient record system and poor environmental conditions at the health center; b) health care provider factors: such as limited awareness of current clinical guidelines and a resistant attitude to adopting new recommendations; and c) Users: challenges with accessing ANC, poor recognition amongst women about the purpose and importance of the specific interventions provided through ANC, and widespread perception of an unfriendly environment at the health center. Conclusions: The ANC package in Mozambique is not being fully implemented in the three study facilities, and a major barrier is poor functioning of the supply chain system. Recommendations for improving the implementation of antenatal interventions include ensuring clinical protocols based on the ANC model. Increasing the community understanding of the importance of ANC would improve demand for high quality ANC services. The supply chain functioning could be strengthened through the introduction of a kit system with all the necessary supplies for ANC and a simple monitoring system to track the stock levels is recommended.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Cabo Delgado; GP - Tete; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

N’weti’s Community Scorecard Experience in Nampula: a Case Study - Franco, Erika Lopez; Dumangane, Sansão (Institute of Development Studies and N'weti, 2015)
This case study was commissioned by N’weti Comunicação para a Saúde to explore the changes emerging from the implementation of an adapted version of the Community Scorecard (CSC) tool in 11 health facilities catchment areas in Nampula. This case study discusses how N’weti has adapted the Community Scorecard (CSC) tool to better improve the quality of the participation and prospects of accountability for citizens. The case study presents evidence that the adapted CSC tool has resulted in an increased awareness of rights, an improved relationship with the service providers, a revitalisation of the health unit Co-management Committees, citizens feeling that their voice is being heard, and N’weti is recognised by people and authorities as catalyser and legitimate mediator of this voice. However, challenges also surfaced which N’weti must reflect and learn from. The first relates to the meaningful control from regular citizens (rather than NGO staff members) of the institutionalisation, follow-up of commitments and advocacy actions derived from the implementation of a CSC process. Other challenges refer to social exclusion, the lack of a deeper understanding of power dynamics, and the fact that ignoring previous histories of citizen engagement and other contextual factors can be misleading as not all change can be directly attributed to the implementation of the CSC.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Meconta; GD - Moma; GD - Rapale; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Measuring Coverage in MNCH: Testing the Validity of Women's Self-Report of Key Maternal and Newborn Health Interventions during the Peripartum Period in Mozambique - Stanton, Cynthia K.; Rawlins, Barbara; Drake, Mary; dos Anjos, Matias; Cantor, David; Chongo, Lidia; Chavane, Leonardo; da Luz Vaz, Maria; Ricca, Jim (PLoS ONE, 2013)
Background: As low-income countries strive to meet targets for Millennium Development Goals 4 and 5, there is growing need to track coverage and quality of high-impact peripartum interventions. At present, nationally representative household surveys conducted in low-income settings primarily measure contact with the health system, shedding little light on content or quality of care. The objective of this study is to validate the ability of women in Mozambique to report on facility-based care they and their newborns received during labor and one hour postpartum. Methods and Findings: The study involved household interviews with women in Mozambique whose births were observed eight to ten months previously as part of a survey of the quality of maternal and newborn care at government health facilities. Of 487 women whose births were observed and who agreed to a follow-up interview, 304 were interviewed (62.4%). The validity of 34 indicators was tested using two measures: area under receiver operator characteristic curve (AUC) and inflation factor (IF); 27 indicators had sufficient numbers for robust analysis, of which four met acceptability criteria for both (AUC .0.6 and 0.75,IF,1.25). Two of these indicators are considered high demand and are recommended for incorporation into international survey programs: presence of a support person during labor/delivery and placement of the newborn skin to skin against the mother. Nine indicators met acceptability criteria for one of the validity measures. All 13 indicators are recommended for use in in-depth maternal/newborn health surveys. Conclusions: Women are able to report on some aspects of peripartum care. Larger studies may be able to validate some indicators that this study could not assess due to the sample size. Future qualitative research may assist in improving question formulation for some indicators. Studies of similar design in other low-income settings are needed to confirm these results.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

How active citizens can make a difference to improving service delivery in Mozambique: Phase 1: mapping citizen engagement programmes, initiatives and experiences - Programme, Citizen Engagement (2013)
The Citizen Engagement Program (CEP) supports citizens to monitor the quality of health and education service delivery in 4 of the 11 provinces of Mozambique, as well as to advocate for the improvement of the quality of those services at the district, provincial and national levels. The CEP aims at contributing towards the increased availability of relevant information for citizens to better access and benefit from services delivered by the public sector; improving citizens' capacity to assess service delivery and engage with service providers to improve the quality of health and education services at the primary and secondary levels; and supporting civil society organizations to leverage those findings within decision-making processes at higher levels. The programme will facilitate the dialogue between citizens / communities and service providers to improve the quality of services. The programme supports capacity-building, learning and experimentation, and will develop a robust system of monitoring and evaluation. The CEP will also analyse and build on experiences of service monitoring carried out by other actors and programmes, including other DFID and Irish Aid funded activities.
Accepted: 2017-12-05T13:07:47Z Publisher: (CEP) Citizen Engagement Programme / Cidadania e Participação
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; citizenship & participation / cidadania e participação; decentralization / descentralização; gender / género; health / saúde; ⛔ No DOI found

Juventude(s) e AIDS em Moçambique: Um Estudo Qualitativo no Distrito de Nhamatanda - Chicamisse, Francisco Armindo Zinhame (Universidade Federal de São Paulo, 2013)
O presente estudo pretende compreender como são desenvolvidas as ações de prevenção do HIV do Programa Geração Biz (PGB) direcionadas aos jovens dos 15-24 anos e, dessa forma buscar a compreensão da possível vulnerabilidade destes a infecção pelo HIV no distrito de Nhamatanda em Moçambique. Para o alcance deste desiderato baseei-me numa abordagem qualitativa, embasada no método etnográfico. No processo de coleta de dados privilegiei a observação participante, complementada por entrevistas semi-estruturadas e uma extensiva pesquisa bibliográfica. No distrito de Nhamatanda os jovens dos 15-24 anos constituem um dos segmentos populacionais mais afetados pelo HIV/AIDS, com uma taxa de prevalência estimada em 30,5% no ano de 2007, sendo por isso considerado um dos grupos mais vulneráveis a infecção pelo HIV. As ações de prevenção do HIV voltadas para este grupo são desenvolvidas pelo PGB, através das suas três componentes: escolar, comunitária e clínica. Entretanto, estas ações ainda estão assentadas na premissa de que a simples transmissão de informação implica na mudança de comportamentos dos jovens. Ademais, as ações de prevenção acabam tendo por vezes um caráter setorial e descontínuo, o que não permite o alcance de resultados mais duradouros no âmbito da prevenção do HIV. Os resultados deste estudo sugerem que as ações de prevenção do HIV ainda não se têm traduzido na redução considerável da referida vulnerabilidade dos jovens (15-24) a infecção pelo HIV neste distrito. Estas ações colocam por vezes os jovens em situações de maior suscetibilidade a infecção pelo HIV. Portanto, há uma necessidade de se repensar no modo como estas ações têm sido operacionalizadas, reelaborar os modelos pedagógicos que as norteiam e adequar os conteúdos semânticos das mensagens em função dos diferentes contextos socioculturais em que a epidemia se espraia.
Keywords: G - Mozambique / Moçambique; G - central / centro; GD - Nhamatanda; GP - Sofala; Health PEA; L - portuguese / português; access to services / acesso a serviços; health / saúde; youth / juventude

“Não basta introduzir reformas para se ter melhores serviços públicos”: subsídio para uma análise dos resultados das reformas no subsector de água rural em Moçambique - Forquilha, Salvador (Desafios para Moçambique 2013, 2013)
Em Setembro de 2012, o Governo de Moçambique anunciou a mudança de critérios para o cálculo das taxas de cobertura de abastecimento de água nas zonas rurais. Com efeito, de 500 pessoas para um poço ou furo equipado com uma bomba manual, num raio de 500 metros, passou -se para 300 pessoas para um poço ou furo equipado com uma bomba manual. Esta mudança de critérios acontece mais de 15 anos depois da aprovação da Política Nacional de Águas (PNA) e resulta da constatação de que, em muitos casos, os números oficiais estão longe de reflectir o que realmente se passa no terreno em termos de taxas de cobertura. Uma das consequências imediatas desta medida é, provavelmente, a revisão em baixa das taxas de cobertura de abastecimento de água rural, o que vai reforçar a ideia de que, à semelhança do que acontece com outros serviços públicos, o abastecimento de água rural ainda está longe de satisfazer as reais necessidades das populações.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; health - WASH / saúde - água; higiene e saneamento; rural development / desenvolvimento rural; ⛔ No DOI found

The Effects of Sector Characteristics on Accountability Relationships in Service Delivery - Mcloughlin, Claire; Batley, Richard (Social Science Research Network, 2012)
Why do different services encounter particular constraints and opportunities in their delivery? This working paper identifies a set of characteristics that can be used to differentiate between services, and between functions within them, and asks how these defining or ‘fixed’ characteristics may influence key relationships of accountability and control.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização

Promoting Respectful Maternity Care in Mozambique - Reis, Veronica (USAID, 2012)
The objective of this document is to share the results of work undertaken in Mozambique to promote respectful health care, particularly in maternal and neonatal care. With its origins in “humanization of care” efforts in Latin America, this approach centers on the woman and her family and is grounded by principles of ethics and respect for human rights. The approach recognizes a client’s cultural background, and views the client as a person with values and expectations that should be respected during the provision of health care. Respectful maternity care (RMC) emphasizes the fundamental rights of the mother, newborn, and family, and recognizes that childbirth is a deeply personal experience for each woman and her family. In addition, RMC ensures that the client has timely access to health information, privacy, and evidence-based care. Promoting RMC can result in many benefits, including increased service utilization and better health outcomes. It is known that women refuse care from health providers who treat them poorly, even if these providers are capable of preventing or managing obstetric or newborn complications. In countries where a large proportion of births occur outside health facilities, RMC can contribute to increased uptake of maternal and newborn health (MNH) services.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Abastecimento De Água Nas Zonas Rurais: Avaliação Dos Progressos Para a Prestação De Serviços Sustentáveis - Munguambe, Carlos Gideon José; Jesus, Vitória Afonso Langa de (IRC International Water and Sanitation Centre, 2011)
This study presents an analytical ‘picture’ of the rural water sub-sector in Mozambique, describing the legal framework, mechanisms for coordination, harmonisation, funding, accountability, participation and supervision. The study was commissioned for the Sustainable Services at Scale, or Triple-S, initiative, which aims to contribute to improving the sustainability of global rural water supply. According to the general population census carried out in 2007, Mozambique had a total population of 20,226,296, 70.2% of whom live in rural areas, with a water coverage rate of only 54%.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; decentralization / descentralização; health - WASH / saúde - água; higiene e saneamento; health / saúde

“All I Eat Is ARVs:” The Paradox of AIDS Treatment Interventions in Central Mozambique - Kalofonos, Ippolytos Andreas (Medical Anthropology Quarterly, 2010)
The number of people on antiretroviral treatment in Mozambique has increased by over 1,500 percent since it first became free and publicly available in 2004. The rising count of “lives saved” seems to portray a success story of high-tech treatment being provided in one of the poorest contexts in the world, as people with AIDS experience dramatic recoveries and live longer. The “scale-up” has had significant social effects, however, as it unfolds in a region with a complicated history and persistent problems related to poverty. Hunger is the principal complaint of people on antiretroviral treatment. The inability of current interventions to adequately address this issue leads to intense competition among people living with HIV/AIDS for the scarce resources available, undermining social solidarity and the potential for further community action around HIV/AIDS issues. Discourses of hunger serve as a critique of these shortcomings, and of the wider political economy underlying the HIV/AIDS epidemic.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Relatório Final da Pesquisa sobre o Impacto da Descentralização dos Fundos Sectoriais de Estradas, Águas e de Construção Acelerada de Salas de Aulas nas Províncias, nos Distritos e nas Autarquias Locais - Kulipossa, Fidelx Pius; Nguenha, Eduardo Jossias (The Open University consultancy, 2009)
A 17a Sessão Ordinária do Conselho de Ministros realizada em 2007 tomou a corajosa decisão de descentralizar os fundos dos sectores de estradas, águas, agricultura, e infra-estruturas de educação e saúde para garantir a implementação efectiva da Lei 8/2003 sobre os Órgãos Locais do Estado e materializar os objectivos estratégicos definidos no PARPA II e no Plano Quinquenal do Governo. Tal decisão, em parte, reconhece que a pobreza absoluta que flagela muitos cidadãos está estreitamente ligada à falta de acesso aos serviços básicos tais estradas, água potável, infra-estruturas escolares e de saúde e outros serviços úteis para a sobrevivência e sustentabilidade da vida humana. Com efeito, presumia-se que ao se descentralizar estes fundos sectoriais para os níveis provinciais e distritais, as instituições locais teriam maior capacidade de resposta às demandas da população em termos de prestação de melhores serviços, de maneira que ela estivesse mais satisfeita e participasse activamente na vida política e económica do país. Em termos de produção legislativa, regista-se avanço significativo na descentralização de fundos sectoriais. Porém, sendo essa legislação muito recente e em fase primária de sua implementação, constatam-se algumas reservas na implementação efectiva da mesma. Por exemplo, os progressos sectoriais na descentralização de fundos são diferenciados. No sector de estradas, os fundos são geridas e os pagamentos efectuados a partir do nível central através da Administração Nacional de Estradas (ANE). Relativamente aos sectores de água e de educação (construção acelerada de salas de aulas) os fundos são geridos a nível provincial e os pagamentos feitos nos dois níveis: provincial e distrital. A leitura do processo, e com respeito às constatações feitas nas províncias de Nampula e Gaza, onde decorreu o trabalho de campo, revelou diferenças peculiares nos avanços e na forma de abordagem da descentralização nas duas províncias, particularmente nos aspectos referentes a critérios de planificação, definição de prioridades, alocação de recursos e fluxos financeiros. As diferenças verificadas para as duas províncias, que podem ser explicadas, em parte, pela diferença de maturidade na condução dos processos de descentralização entre Nampula e Gaza, sendo a primeira mais experiente, não inibem concluir que, em termos gerais: (1) a descentralização de fundos sectoriais ainda não é efectiva; (2) o envolvimento das instituições de planificação e consulta comunitária é efectivo; (3) o sistema de prestação de contas é complexo, moroso e contraproducente; (4) o sistema de monitoria e avaliação ao nível distrital pode ainda ser melhorado; (5) a capacidade de manutenção ao nível distrital precisa de fortalecimento; (6) há fraco envolvimento do sector privado na prestação de alguns serviços; (7) há desarticulação institucional na aplicação de alguma legislação; (8) os critérios de atribuição de fundos sectoriais são inconsistentes e pouco divulgados; e (9) há, nos distritos, falta de uma perspectiva multisectorial e sistemática de planificação. Face aos problemas identificados, este Relatório Final propõe algumas recomendações: nova abordagem sobre os fundos sectoriais, particularmente a sua integração nos PESOD; alinhamento dos instrumentos de planificação estratégicos locais com os nacionais; regulação em legislação própria dos critérios de alocação de fundos, capacitação institucional entre outras acções.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; access to services / acesso a serviços; decentralization / descentralização; education / educação; infrastructure - roads / infrastructura - estradas

Programas de saúde materno-infantil em Moçambique: marcos evolutivos e a inserção da enfermagem (Programs of maternal and infant health in Mozambique: gradual landmarks and the insertion of nursing) - Lourenço, Maria Acácia Ernesto; Tyrrell, Maria Antonieta Rubio (Escola Anna Nery, 2009)
See english abstract below. Pesquisa centrada nas políticas públicas do governo moçambicano para o setor da saúde, com foco voltado para programas de assistência à saúde materno-infantil. Tem o propósito de apresentar contextos básicos para a reflexão sobre a filosofia da implantação e implementação dos programas e a inserção da Enfermagem, mostrando seus marcos evolutivos. Constatou-se que, na década 70, o Sistema Nacional de Saúde adotou o Programa de Proteção Materno-Infantil, que na década de 80 ficou concebido como Programa de Saúde Materno-Infantil e, posteriormente, na década 90, ficou inserido no Programa Nacional Integrado de Saúde Materno-Infantil e Planejamento Familiar, Programa Alargado de Vacinação, Saúde Escolar e do Adolescente, incluindo Saúde Sexual e Reprodutiva. A inserção da Enfermagem foi evidenciada na implementação das ações assistenciais. Os marcos evolutivos foram: a introdução dos cursos específicos de Enfermagem em saúde materno-infantil do nível básico ao superior e abrangência dos serviços do Programa Nacional Integrado. ABSTRACT For the interest to know about the public Policies of Mozambican government to the Health sector, this research put much emphasis on the process of implantation and implementation of assistance programs to maternal health looking at reflection about the philosophy of including nursing through ever-changing world or marked changes. Established in the 1970s, the National Health System came up with a maternal health protection program which in the 1980s was drawn into Maternal Health Program. This, in the 1990s was included in the National integrated program of maternal health and family planning, integrating a broad vaccination program, school health and adolescent sexual reproductive health. The inclusion of nursing in the implementation of integrated program became as the evidence through action assistances. The evolutional signs were the introduction of specific courses of Maternal and Infant Health Nursing from basic to superior levels, including the service of National Integrated Program.
Publisher: UFRJ
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - portuguese / português; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Collaboration and competition in a children's health initiative coalition: A network analysis - Valente, Thomas W.; Coronges, Kathryn A.; Stevens, Gregory D.; Cousineau, Michael R. (Evaluation and Program Planning, 2008)
Activating communities to achieve public health change and initiate policy reform usually requires collective action from many entities. This case study analyzes inter-organizational networks among members of a coalition created to expand health insurance coverage to uninsured children in a large metropolitan area. Six networks were measured: collaboration, competition, formal agreements, receive funding from, send funding to, and greater communication. The response rate was 65.8% (50 of the 76 active members). Positive network questions such as “who do you collaborate with” elicited many network choices whereas negative ones such as “who do you compete with” elicited few. The collaboration network had a core–periphery structure and analysis showed that a large network can be reduced to a small set of core organizations one-sixth the size of the whole. Centrality (out- and in-degree) was associated with perceived organizational function and perceived barriers to success. For example, organizations that received many choices as collaboration partners were more likely to perceive the coalition functioned well than those who received few choices. The study suggests that perceptions of organizational performance are associated with position in the network, central members are more likely to perceive the organization performs well than those on the periphery.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; M - methodology / metodologia; access to services / acesso a serviços; collaboration / colaboração; health - maternal and child / saúde - materno-infantil; health / saúde

Consultoria sobre a Abolição das Taxas aos Utilizadores do Serviço Nacional de Saúde (SNS) em Moçambique - Cabral, Antonio Jorge Rodrigues (Instituto de Higiene e Medicina Tropical da Universidade Nova de Lisboa, 2007)
Existem actualmente taxas de utente cobradas em grande parte dos serviços de saúde públicos, em Moçambique. No entanto, historicamente, o partido no poder, a FRELIMO, tem sido bastante favorável a uma situação de serviços básicos de saúde gratuitos, e considera que a eliminação de barreiras de acesso à educação e saúde básicas constituem elementos fundamentais da estratégia de redução de Pobreza e de êxito nas Metas de Desenvolvimento do Milénio. O Governo de Moçambique considera ainda que a permanência das taxas mantém aberta a porta para a cobrança de taxas ilegais. A experiência de países vizinhos e a eliminação das taxas de matrícula no Ensino Básico em Moçambique constituíram motivações adicionais aos responsáveis do sector para que a viabilidade da remoção das taxas fosse avaliada. Esperava-se desta consultoria: i) uma avaliação da aplicação actual das taxas de utente; ii) uma síntese sobre o provável impacto esperado da abolição das taxas de utente nos serviços básicos de saúde em Moçambique, em especial na carga de trabalho dos funcionários da saúde e nos custos recorrentes no Sector da Saúde; iii) uma síntese dos pontos de vista da população em relação as condições de acesso aos cuidados de saúde, e dos pontos de vista de outros intervenientes em relação as taxas de utente no sector da saúde.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

War and reconstruction in northern Mozambique - Brück, Tilman (The Economics of Peace and Security Journal, 2006)
The article discusses some of the economic effects of war in northern Mozambique. It indicates how the historical and structural features of the economy of northern Mozambique restricted post-war reconstruction and post-war poverty alleviation. These features include the dominance of only a few cash crops for export, the absence of much rural trading, poor communication infrastructure, and weak political and state institutions. The specific nature of the internal war further weakened the state through the collapse of tax revenue and export earnings and the massive growth of debt and aid, of which little reached rural northern Mozambique. The article also summarizes key aspects of the geography, climate, markets, and social institutions of northern Mozambique, which define the potential production opportunities for peasant households. Finally, the article suggests how post-war reconstruction could have been more effective in achieving faster post-war poverty alleviation in northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; conflict - civil war / conflito - guerra civil; health / saúde

Improving Health for the Poor in Mozambique: The Fight Continues - Chao, Shiyan; Kostermans, Kees (International Bank for Reconstruction and Development / The World Bank, 2002)
The health sector in Mozambique has made significant progress in terms of increasing coverage of services. However, health remains a major concern in the area of poverty reduction. The study describes the health status of the population, especially of the poor, and how the sector responds to the needs. Huge inequalities continue to exist with regards to resource allocation, deployment of staff and availability of services among various geographic areas, between the urban and rural population, and between the poor and the non-poor. The study builds upon the existing studies on health and consolidates the sector knowledge. Based on the analysis, the study makes various recommendations on how the health sector reforms can be made more pro-poor by focusing on certain interventions, by targeting certain areas and population groups, by designing new delivery models that would bring the services closer to the population, and by improving financial management to serve the poor more effectively.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; health / saúde; poverty / pobreza

A study of the actual and potential usage of information and communication technology at district and provincial levels in Mozambique with a focus on the health sector - Braa, Jørn; Macome, Esselina; Mavimbe, João Carlos; Nhampossa, José Leopoldo; da Costa, João Leopoldo; José, Bonifacio; Manave, Aurélia; Sitói, António (The Electronic Journal of Information Systems in Developing Countries, 2001)
This article presents results from a study on the use and appropriation of information and communication technologies (ICT) in Mozambique with a focus on the health sector. The three provinces of Gaza, Inhambane and Niassa were surveyed and two questionnaires addressing 1) computer users and their ability to manage ICT, and 2) health workers and their handling of health information, were used. Based on this study appropriate strategies for developing an ICT-infrastructure with the needs of the health sector as points of departure are discussed. The study is born out of a program to strengthen and further develop the health information and management systems at district and provincial levels as part of a process to support decentralisation of the health system in Mozambique. The study shows that computers and Internet are rapidly being spread to the provincial capitals and major districts in Mozambique. A main problem identified is the lack of ICT-skills and education and poorly developed infrastructure and networks of support. There are very few formal ICT companies providing hardware, and even less, software support. Maintenance and learning about ICT are to a large extent going on within informal networks of computer users in the provinces. A main finding in this study is that development of ICT capacity and information systems at district and provincial levels in Mozambique needs to be an integrated effort across sectors. A district health information system cannot be developed in a void. A general recommendation is to develop educational programmes ranging from training of ICT entrepreneurs and health workers and managers, to Masters and PhD programmes in ICT and health information systems. A specific recommendation related to health information systems development is to focus on the district level and to develop a strategy which encompasses and integrates all districts, both the advanced districts with computers and the majority of the districts where there are no computers.
Publisher: Wiley Online Library
Keywords: *indexed; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; health - health information systems / saúde - sistema de informação de saúde; health / saúde

Microlearning Resource: Changing How Services Are Delivered So Fewer Patients Come to Health Facilities in the Context of COVID-19 Pandemic | Global Financing Facility
In this learning object you will be able to: Explore the changes needed in service delivery to reduce the number of patients who go to health facilities. Identify good practices in terms of the role of Community Health Workers to provide services, use of digital and telemedicine services, and Family Planning modeling and use of private sector to deliver services. Reflect about possible required changes in participating countries’ health services.
Keywords: Health PEA; L - english / inglês; access to services / acesso a serviços; health - COVID-19 / saúde – COVID-19; health / saúde